Practice patterns and outcomes with the use of regorafenib in metastatic colorectal cancer: Results from the Regorafenib in Metastatic colorectal cancer - An Indian exploratory analysis study - Anant Ramaswamy (South Asian Journal of Cancer, 2019)
Background: Regorafenib is considered a standard of care as third-line therapy in metastatic colorectal cancers (mCRCs). Materials and Methods: The study was based on a computerized clinical data form sent to oncologists across the country for entry of anonymized patient data. The data entry form was conceived and generated by the coordinating center's (Tata Memorial Hospital) gastrointestinal medical oncologists and disseminated through personal contacts at academic conferences as well as through E-mail to various oncologists across India. Results: A total of 19 physicians contributed data resulting in 80 patients receiving regorafenib who were available for the evaluation of practice patterns. The median age was 55 years (range: 24–75). Majority had received oxaliplatin-based (97.5%), irinotecan-based (87.5%), and targeted therapy (65%), previously. Patients were primarily started on reduced doses of regorafenib upfront (160 mg – 28.8%, 120 mg – 58.8%, and 80 mg – 12.5%). The median duration of treatment (treatment duration) with regorafenib was 3.1 months (range: 0.5–18), while the median progression free survival was 3.48 months (range: 2.6–4.3). Forty-five percent of patients required dose modifications due to toxicities, and the most common were (all grades) hand-foot syndrome (68.8%), fatigue (46.3%), mucositis (37.6%), and diarrhea (31.3%). Conclusions: Majority of physicians in this collaborative study from India used a lower dose of regorafenib at the outset in patients with mCRC. Despite a lower dose, there was a significant requirement for dose reduction. Duration of treatment with regorafenib as an efficacy end point in this study is similar to available data from other regions as it is the side effect profile.